Separation of Enzymes from their Aqueous System by using Novel Concept of Unidirectional Freezing - Mushtaq, Muhammad Waheed; Younas, Muhammad Waqar; Anwar, Jamil; Abbas, Syed Mustansar; Bashir, Shahid (Zoological Society of Pakistan, 2019)
In our present work, the separation and extraction of three different enzymes (alpha-amylase, cellulase and pectinase) from aqueous system has been studied by applying novel concept of unidirectional freezing. To separate the enzymes from their aqueous system, directional freezing was applied horizontally through synthetic enzyme contaminated water samples, called radial freezing. After complete freezing, the samples were collected from various sections of the frozen mass and concentration of enzymes was determined. It was found that more than ∼85% mass of enzymes, migrated along with freezing front and concentrated in the centre in case of radial freezing. To examine the effect of unidirectional freezing over extracted enzymes, the working activity of separated enzymes was checked by performing desizing test for alpha-amylase and biopolishing test for cellulase. The noteworthy results of desizing and biopolishing test has promoted the significance of unidirectional freezing technique (UFT). Copyright © 2019 Zoological Society of Pakistan.